Experimental study on deformation and failure mechanism of the double-arch tunnel without a middle pilot - Zhao, Jiang; Tian, Wen-Ling; Zhang, Ben-Qing; Yang, Sheng-Qi (Frontiers in Earth Science, 2025)
To explore the deformation and failure mechanism of multi-arch tunnel without a middle pilot tunnel, taking the Sanyanjing tunnel of Qiuyan Expressway in Yunnan province as the research object. The stress evolution and the associated deformation and failure mechanisms of the surrounding rock, composed of class IV limestone, were studied using a physical model test during the excavation process. The results show that tangential stress attenuation occurs within a distance equal to the diameter of the tunnel wall, while stress concentration occurs beyond this range in the unsupported tunnel. However, the supporting structure, forms a stable pressure arch within the surrounding rock, which makes the elastic zone extend to the surrounding and deep of the tunnel. The surrounding rock at the top of the middle wall in the unsupported tunnel shows the trend of linear decrease of horizontal stress and rapid linear increase of vertical stress. Meanwhile, vertical stress remains relatively stable, whereas horizontal stress exhibits a pronounced “bias effect.” The tunnel invert and the outer arch foot are identified as vulnerable structural components, necessitating close attention to lining strength and construction quality.